ประสิทธิผลของการดำเนินโครงการนำนักเรียนเข้าเรียนรู้ในสวนสัตว์เชียงใหม่ ประจำปีงบประมาณ พ.ศ.2554-2555 - ชวนพิศ ชัยประยูร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This research was Effectiveness of “ZooSchool Project” Implementation of Chiang Mai, Fiscal Year B.E. 2554-2555. The objectives of this study were 1) to analyze the relationship between policy and effectiveness of “ZooSchool Project” Implementation of Chiang Mai Zoo 2) to analyze the result of project management towards effectiveness of “ZooSchool Project” Implementation of Chiang Mai Zoo 3) to analyze the result of courses attraction towards effectiveness of “ZooSchool Project” Implementation of Chiang Mai Zoo 4) to study the impact of the occurrence of new knowledge competitors that were similar to this project towards effectiveness of “ZooSchool Project” Implementation of Chiang Mai Zoo. This research was a qualitative research which was a comparative study about the system of educational administration. The study were found that (1) the policy; there was the executive policy which was supportive the effectiveness of educational management within Chiang Mai Zoo followed The National Education Act on “Government must promote the implementation and the establishment of lifelong learning resources in all forms as information and learning resources sufficiently and efficiently” that were the main objective of The National Education Act (2) the project management process; there were using a participatory process between students and the officials by many activities so that the result of learning and practice of students could be developed by doing activities (3) the courses attraction and the suitable implementation affect effectiveness of the project; there were setting the curriculum to promote learning in 8 groups to integrated with learning component of the zoo and focus on the group of learners and the difficulty of the activity sheet was created by realizing the potential of students (4) competitors learning resources; Chiang Mai Zoo had a distinctive reputation. The famous animals were pandas and koalas. The competitors were from the management sectors because most competitors had the form of private management with the capacity to developed quickly. In view point of interviewees, they had the opinion that any large organization usually had a slow movement, especially in the management to developed the organization and any small or moderate organization always developed the management of organization agilely. The suggestion of this research were (1) public relations should be promoted in many processes as in the parallel system (2) development of personnel skills, promotion of the role of resources management to be wider, the database should be created up to the standard level, and making partnerships with both external and internal agencies (3) funding from external and internal organizations to get enough budget for development, particularly in media innovations.